Implementation of Game-Based Learning (Word Wall) to develop English language mastery for Elementary Students - Syifana Alifah Muazarah; Melfany Syifa Adeline; Meysa Aulia Putri (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to apply game-based learning using the Word Wall method in developing the English language skills of fourth-grade students at SDN Nusa Indah 01. The background of this study focuses on the importance of English language skills in the era of globalization, where foreign language skills are one of the keys to competing in the world of education and work. The research methods used include open-ended and closed-ended questionnaires for students and teachers, in-depth interviews, and observations or field notes. The questionnaires were designed to measure the effectiveness of the learning process and the responses of students and teachers to the applied method. The research results indicate that the use of Word Wall as a game-based learning medium successfully increased students' interest and motivation in learning English. Additionally, in-depth interviews revealed that teachers also felt the positive impact of this method in the learning process. The conclusion of this research is that game-based learning is effective in improving students' English language skills, as well as providing an enjoyable and interactive learning experience. The implementation of the Word Wall method also contributed to strengthening students’ vocabulary retention. Through visual and kinesthetic engagement, students were more likely to remember new words, use them in context, and demonstrate improved pronunciation. Classroom observations indicated that students became more confident in expressing themselves in English, especially during interactive activities such as group games, matching words, and storytelling using the vocabulary displayed on the Word Wall. This method provided repeated exposure to target vocabulary in a meaningful and engaging way.